Clinical Effectiveness of Hypofractionated Proton Beam Therapy for Liver Metastasis From Breast Cancer - Kim, Tae Hyun; Lee, Keun Seok; Sim, Sung Hoon; Kim, Yeon-Joo; Kim, Dae Yong; Chae, Heejung; Lee, Eun-Gyeong; Han, Jai Hong; Jung, So Youn; Lee, Seeyoun; Kang, Han Sung; Lee, Eun Sook (Frontiers in Oncology, 2021)
Background: Few studies of proton beam therapy (PBT) for patients with liver metastasis from breast cancer (LMBC) are available to date. The aim of the present study was to evaluate the clinical effectiveness of PBT for patients with LMBC. Material and Methods: Seventeen patients with LMBC treated with PBT were included in this study. The median prescribed dose of PBT was 66 GyE (range, 60–80) in 10 fractions, 5 times a week. In patients with LMBC receiving PBT, freedom from local progression (FFLP), progression-free survival (PFS), and overall survival (OS) rates were assessed. Results: The median follow-up time was 34.2 months (range, 11.5–56.1). The median FFLP time was not yet reached, and the 3-year FFLP rates were 94.1% (95% confidence interval [CI], 82.9–105.3). The median times of PFS and OS were 7.9 months (95% CI, 5.3–10.5) and 39.3 months (95% CI, 33.2–51.9), respectively, and the 3-year PFS and OS rates were 19.6% (95% CI, -1.8–41.0) and 71.7% (95% CI, 46.8–96.6), respectively. Grade 3 or higher adverse events were not observed. Conclusion: PBT for patients with LMBC showed promising FFLP and OS with safe toxicity profiles. These findings suggest that PBT can be considered a local treatment option in patients with LMBC.